1999
DOI: 10.1002/(sici)1097-4547(19990301)55:5<533::aid-jnr1>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological role of calpain in experimental demyelination

Abstract: Calcium-activated neutral proteinase (calpain) has been extensively studied over the past three decades such that many enzymatic and structural properties of this enzyme are well understood. However, the pathophysiological roles of calpain remain poorly defined. In addition to recent studies delineating a role for calpain in various pathological conditions, this proteinase has been implicated in the degradation of myelin proteins in autoimmune demyelinating diseases such as multiple sclerosis and experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 66 publications
1
26
0
Order By: Relevance
“…Several lines of evidence indicate that only p25 but not p35-bound cdk5 phosphorylates tau in vitro, thereby inducing pathological alterations in neurons (22-25, 40, 41). It is interesting to note that conversion of p35 to p25 is regulated by the calcium-dependent cysteine protease calpain as activation of calpain together with impaired calcium homeostasis has been observed in EAE and MS brains (42,43). It is therefore tempting to speculate that increased calcium influx might trigger a cascade of pathological events that lead to calpain activation, followed by conversion of p35 to p25 and increased and pathological tau phosphorylation at epitopes such as PHF-1, AT-8, and AT-100.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence indicate that only p25 but not p35-bound cdk5 phosphorylates tau in vitro, thereby inducing pathological alterations in neurons (22-25, 40, 41). It is interesting to note that conversion of p35 to p25 is regulated by the calcium-dependent cysteine protease calpain as activation of calpain together with impaired calcium homeostasis has been observed in EAE and MS brains (42,43). It is therefore tempting to speculate that increased calcium influx might trigger a cascade of pathological events that lead to calpain activation, followed by conversion of p35 to p25 and increased and pathological tau phosphorylation at epitopes such as PHF-1, AT-8, and AT-100.…”
Section: Discussionmentioning
confidence: 99%
“…In the acute Lewis rat model of EAE, calpain expression was correlated with T cell, macrophage, and neutrophil migration into the CNS [193]. Examination of the acute EAE spinal cord revealed that Ca 2+ influx and calpain expression correlated with axonal damage, mitochondrial damage, and loss of structural integrity of microtubules and filaments [187].…”
Section: Cytokine-based Immuno-interventionmentioning
confidence: 99%
“…Indeed, several laboratories have shown that degradation of cytoskeletal proteins occurs in experimental models of stroke (Aronowski et al, 1999;Hong et al, 1994;Liebetrau et al, 1999;RobertsLewis et al, 1994), TBI Kampf et al, 1996;Newcomb et al, 1997;Posmantur et al, 1996;Saatman et al, 1996a), spinal cord injury (Banik et al, 1997;Braughler and Hall, 1984;Ray et al, 1999), and experimental allergic encephalomyelitis (EAE), a model of the demyelinating disease, multiple sclerosis (for review, see Shields and Banik, 1999). While damage to cytoskeletal proteins (e.g., neurofilaments, microtubule-associated protein, a-spectrin) is evident within the first minutes following experimental TBI, the height of proteolytic activity appears to occur several hours after injury (Newcomb et al, 1997;Posmantur et al, 1994), and in the case of mild injury, occurs as late as several days (Saatman et al, 1998).…”
Section: Introductionmentioning
confidence: 99%